Effect of welding speed on performance of friction stir welded spray forming 7055 aluminum alloy. (October 2019) - Ma, Shengchong; Zhao, Yong; Pu, Jihong; Zhao, Zhixia; Liu, Chuan; Yan, Keng
Graphical abstract: Highlights: Effect of welding speed on performance of FSWed spray formed AA 7055 was studied. The microstructure and phase in different regions of the joint were analyzed. The relationship between the hardness profiles and precipitation was investigated. Abstract: With the increase of welding speed from 75 to 150 mm/min, the grain size of the nugget zone first decreased and then increased, and the smallest grain size was obtained at 100 mm/min. The maximum tensile strength of 445 MPa was achieved at the welding speed of 100 mm/min, equivalent to 70% of the base metal. The hardness value of the heat-affected zone increased with the rising welding speed. Joint hardness was affected by precipitated phases and it decreased overtly from thermo-mechanically affected zone to heat-affected zone. Owing to the fact that a number of big precipitates clustered in the heat-affected zone, the strengthening effect in spray formed ultra-high strength 7055 aluminum alloy was weakened which caused the hardness of the joint to reduce remarkably. Because of the recrystallization, most of the phases in nugget zone were dissolved and the rest were similar to those in the base metal, while AlCuMg phase and Al2Cu phase precipitated in heat-affected zone. The phase precipitated in the nugget zone and heat-affected zone decreased gradually with the increase of the welding speed.